Feasibility and efficiency of a new 22G core needle: a prospective comparison study - Hucl, Tomas; Wee, Eric; Anuradha, Sekaran; Gupta, Rajesh; Ramchandani, Mohan; Rakesh, Kalpala; Shrestha, Ramila; Reddy, Duvvuru Nageshwar; Lakhtakia, Sundeep (Endoscopy, 2013)
Background and study aims: Histological examination of core tissue samples may have advantages over cytology in endoscopic ultrasound (EUS)-guided sampling. We aimed to evaluate the feasibility and efficiency of a new 22G core biopsy needle. Patients and methods: Consecutive patients with a pancreatic mass lesion or peri-intestinal lymphadenopathy sequentially underwent fine needle biopsy with both a newly developed 22G core needle (the FNB needle) and a standard 22G fine needle aspiration (FNA) needle, in randomized order.Results: In 144 patients, mean age 48 years (± standard deviation [SD] 14; range 18 – 82), with 145 lesions (mean lesion size 39 ± 15 mm, range 15 – 99), EUS-guided sampling was technically feasible with both needles in all patients. Mean number of passes to obtain sufficient tissue was 1.2 ± 0.5 with the core needle vs. 2.5 ± 0.9 with the standard needle (P < 0.001). FNB specimens were adequate for evaluation in 125 (86.2 %) vs. 127 (87.6 %) with FNA (P = 0.72). Among 139 patients available for follow-up, FNB provided a correct diagnosis in 110 (79.1 %) and FNA in 112 (80.6 %) (P = 0.73). Sensitivity, specificity, positive and negative predictive values, and accuracy for diagnosis of malignancy were 90 %, 100 %, 100 %, 93 %, 96 % for FNB and 77 %, 100 %, 100 %, 85 %, 92 % for FNA, respectively (P > 0.05).Conclusion: FNB with the new 22G core needle was technically feasible, efficient and comparable to FNA with a standard needle. The core needle required fewer passes to provide an adequate sample, offering potentially shorter procedure time.